2019
DOI: 10.1111/nph.15774
|View full text |Cite
|
Sign up to set email alerts
|

Plant species abundance and phylogeny explain the structure of recruitment networks

Abstract: Summary Established plants can affect the recruitment of young plants, filtering out some and allowing the recruitment of others, with profound effects on plant community dynamics. Recruitment networks (RNs) depict which species recruit under which others. We investigated whether species abundance and phylogenetic distance explain the structure of RNs across communities. We estimated the frequency of canopy–recruit interactions among woody plants in 10 forest assemblages to describe their RNs. For each RN, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…(2019) who found that the probability of germination of seeds from 10 species sown under 5 different nurses increased with the trait distance between the nurse and the facilitated species. Altogether, these results validate the premise and support the prediction made by previous studies using phylogenetic as a proxy of phenotypic distances between nurses and facilitated plants (Alcántara et al ., 2018, 2019; Marcilio‐Silva et al 2015; Valiente‐Banuet and Verdú, 2008; Verdú et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) who found that the probability of germination of seeds from 10 species sown under 5 different nurses increased with the trait distance between the nurse and the facilitated species. Altogether, these results validate the premise and support the prediction made by previous studies using phylogenetic as a proxy of phenotypic distances between nurses and facilitated plants (Alcántara et al ., 2018, 2019; Marcilio‐Silva et al 2015; Valiente‐Banuet and Verdú, 2008; Verdú et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, more than a decade after setting the initial assumption of divergent traits favouring facilitation and despite the vast amount of literature looking at trait patterns in facilitation (Butterfield and Callaway, 2013; Le Bagousse‐Pinguet et al 2015; Liancourt and Tielbörger, 2011; Michalet et al ., 2011; Schöb et al ., 2013; Soliveres et al ., 2014), phenotypic distances between species have never been used to explain the structure of plant facilitation networks. Instead, phylogenetic distances – taken as a proxy of trait divergence between species – have become the common procedure to test it (Alcántara et al ., 2018, 2019; Marcilio‐Silva et al 2015; Valiente‐Banuet and Verdú, 2008; Verdú et al ., 2010). Indeed, little empirical research addressing the link between traits and facilitation networks at the community level exists despite the broad consensus that predicting community and ecosystem processes from species traits is a ‘Holy Grail’ in ecology (Lavorel and Garnier, 2002; Funk et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that phylogenetically clustered communities could be produced when competitive ability is evolutionarily conserved and therefore fitness differences instead of niche differences are the main community assembly mechanism (Mayfield and Levine 2007). However, facilitative interactions have been shown to be mainly mediated by niche differences (Valiente‐Banuet and Verdú 2007, Butterfield and Briggs 2011, Alcántara et al 2019a, Navarro‐Cano et al 2019). Including the phylogenetic specificity between interacting plants at the community level could thus shed light on SGH in natural communities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the implications of these patterns for community dynamics are yet to be explored explicitly, they agree with two properties of ecological networks known to confer them stability: (a) that networks containing many weak and few strong interactions are more stable (McCann, Hastings, & Huxel, ; Wootton & Stouffer, ); and (b) that the coexistence of species that differ in fitness requires stronger intra‐ than interspecific limitation of population growth (Chesson, ). At least in the RNs analysed by Verdú and Valiente‐Banuet () and Alcántara, Garrido, and Rey () there is evidence suggesting that the second property may actually be acting in these communities, creating a community compensatory trend whereby more abundant species have lower rates of recruitment than rarer ones (Comita et al., ; Connell, Tracey, & Webb, ; Soliveres et al., ).…”
Section: Introductionmentioning
confidence: 99%